Endometrium at menopause: The pathologist's view - Meenakshi Swain; Aditya D Kulkarni (Wolters Kluwer Medknow Publications, 2021)
Endometrium at menopause is inactive and free of cyclical changes that are characteristics of the reproductive age. At the same time, menopausal endometrium is subject to a variety of disease processes, the most sinister of which are the endometrial malignancies. In the present pictorial review, we briefly discuss the various morphologic patterns of diseases affecting the menopausal endometrium. With an aim to provide insights from the pathologists' point of view, multiple pictures for each of the disorders are shared. We highlight the finer points a pathologist looks for, to ensure proper treatment and welfare of postmenopausal women.